Site Partition Enhanced Shape Based Docking and Molecular Dynamics Studies of G-Protein Coupled Receptor Acting Natural Ligands - Santhanam Vijayasri, Waheeta Hopper (Journal of Applied Pharmaceutical Science, 2018)
The G-protein coupled receptors (GPCR) form a major group of the target for centrally acting drugs. One of the Class C GPCRs, mGluR5 plays a major role in the learning and memory of the brain. Under perturbed conditions, the activity may result in excito-toxicity, neuro-toxicity and also may lead to epilepsy. The competitive ligands for this receptor are in a greater demand in the pharmaceutical industry as the drugs to cure many Central Nervous System (CNS) disorders. A site partition enhanced shape based docking protocol was followed to identify the drug leads from the marine compounds that could competitively bind to the active site of mGluR5. The studies concluded a dienal derivative from Plocamium corallorhiza as the best lead. The molecular dynamics studies were performed for a period of 25 ns. The results were satisfactory on account of receptor-ligand interactions at the molecular level and pharmaco¬kinetic properties. The results suggest that this lead may compete with the control ligand glutamate for the active site and could be a competitive ligand of mGluR5. The binding of this natural ligand to the extra-cellular site of mGluR5 would certainly change its post functions producing a therapeutic effect.
Keywords: Docking, GPCR, LigandFit,Marine, mGluR5, MolecularDynamics.